THE EFFECTIVENESS OF THE PRODUCT DESIGN FOR RELAXATION: A CASE STUDY OF THE SHORT – STAY DEPARTMENT OF THAMMASAT HOSPITAL - Laoharatchatathanin, Kanjana; Punyalikrit, Rueanglada (Fine Arts Journal: Srinakharinwirot University, 2021)
The objective of this study is to examine the product design to create a psychological relaxation for patients recovering in the short-term nursing department. The study is a case study of Thammasat Chalermprakiat Hospital and the subjects are chronic disease patients who receive blood transfusion and chemotherapy treatment. The department organized the project in 1994 with the aims to reduce pain, and medication side effects including exhaustion, fever, chills, and pale all of which cause tension among recovering patients. However, the main problem is that there are no suitable products to help these patients reduce tension. This study, therefore, employs a Quasi–Experimental Research method to collect data from the patients staying in the short-term nursing department. The study examines the satisfaction level of the patients before and after using the product in order to (1) investigate the factors and limitations that affect the stimulation of relaxation conditions, (2) identify the materials that are suitable for the product design and (3) design the products that create a soothing condition for the patients. The findings of the study show that there are several factors including room, smell, shape, texture, and sound of music leading to the patients’ satisfaction of “Rak” products, and “Rak” products can create relaxation for patients in short-term nursing department.